ALTERNATIVE ASSESSMENTS FOR READING IN SENIOR HIGH SCHOOLS: A Guide for Classroom Practices - . Wiyaka; Entika Fani Prastikawati; Jafar Sodiq (Soegijapranata Catholic University, 2016)
One significant difference characterizing the 2013 Curriculum from the former one is the use of authentic assessment to measure the students expected learning outcomes. The old-fashioned mode of assessments such as multiple choice, or completion is regarded insufficient to capture the language skills mastery of the students. Students' demonstration of the mastery of various domains of learning objectives has not necessarily equated with a demonstration of their capacities in real-world settings. Ideally, what is tested should mirror what really is required outside the classroom. So far reading mastery is always tested through traditional mode of assessment like multiple choices (MC). The new curriculum recommends a different perspective of assessment which is called alternative assessment. However, the shift from the traditional assessments to authentic assessments seems to challenge some constraints on the part of the teachers. Many teachers are not quite familiar with the new concepts andpractices within the emerging paradigm. It is due to the absenceof a clear guideline for doing such assessments. The goal of this paper is to propose a theoretically grounded method to conduct alternative assessments which are developed from a pair of standard competences listedin theEnglish syllabus for Senior High School level